Identification and validation of novel QTL associated with powdery mildew (Golovinomyces cichoracearum (DC.) V.P. Heluta.) resistance in sunflower (Helianthus annuus L.): Identification and validation of novel QTL associated with powdery mildew (Golovinomyces cichoracearum (DC.) V.P. Heluta.) resistance in sunflower (Helianthus annuus L.) - DHANALAKSHMI RAJESHWARAN; MANIVANNAN NARAYANA; VISWANATHAN PALANIAPPAN; SASIKALA RAMASAMY; RAJENDRAN LINGAN; SENTHIVELU MUNIYANDI (Journal of Oilseeds Research, 2023)
Sunflower (Helianthus annuus L.; 2n=2x=34) is an important annual oilseed crop cultivated worldwide. In the recent past, powdery mildew disease has evolved as a significant constraint for yield and quality production in sunflower crop. Hence, a F2 mapping population was developed from a cross COSF 15B x IR6 to identify quantitative trait loci (QTL) associated with powdery mildew resistance in sunflower. F2:4 recombinant lines of this population were screened along with parents and scored for powdery mildew resistance during Dec-Feb 2021-22. Per cent disease index (PDI) was calculated from the data taken 75 days after sowing (DAS) using a 0-9 score scale. Genetic linkage map was constructed with 92 SSR markers which covered 1053.3 cM. The QTL analysis resulted in the detection of one QTL in LG10 for PDI. It has 2.54 LOD and accounted for 12.25 per cent phenotypic variation. The flanking markers viz., ORS684 and ORS1110 have a flanking distance of 1.7 cM and validated with a set of population revealed that 24% and 28% PVE respectively. Hence, it may be concluded that markers ORS684 and ORS1110 can be effectively utilized for marker assisted breeding programme to develop the sunflower lines resistant to powdery mildew.